To what extent classroom teacher’s methodology promotes effective classroom discussion for students on the Advanced English level XVII from CENIUES at the University of El Salvador - Carrillo Santos, Willian Amilcar; Arias Pérez, Víctor Antonio; Ramírez Cruz, Allan Adonai; Navidad Morales, Fidel (San Salvador, El Salvador : Universidad de El Salvador, 2014)
Making reference to the role of a teacher a facilitator in different ways, The following research is based on describing some factors that influence the classroom discussion and explain some activities that can help the teacher to improve the effective classroom discussion in their English learning process with students from Advanced English level XVII from the Saturday´s course from CENIUES at the University of El Salvador, and based on different ideas supported by philosophies about the way an English teacher can develop a student in the great skill of speaking as after previous research by Chomsky who proposed and defined the concepts of competence and performance, advocates for a communicative view in applied linguistics (e.g. Savignon, 1972) expressed their strong disapproval at the idea of using the concept of idealized, purely linguistic competence as a theoretical ground of the methodology for learning, teaching and testing languages. They found the alternative to Chomsky’s concept of competence in Hymes’s communicative competence which they believed to be a broader and more realistic notion of competence. The research group took in to account the result of two different English groups from CENIUES to prove that the teacher methodology is fundamental to let in higher proficiency levels perform a group discussion with the everyday topic in the classroom and let knowledge of those students serve as a reference to find the positives ways of applying a good methodology creating the perfect environment of a foreign language as English language.
Tesis (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2014
Bibliografía : hojas 83-86
Keywords: Inglés -- Enseñanza; Métodos de enseñanza; CENIUES